Control previo de los procesos contables en la efectividad de la contratación pública en obras de infraestructura en el gobierno autónomo descentralizado del cantón Guaranda, provincia de Bolívar, año 2017 - Guzmán Garófalo, Jesenia Elizabeth (2017)
With the purpose of contributing to the proper development of public procurement processes in the autonomous government, the following topic was raised: "PRIOR CONTROL OF ACCOUNTING PROCESSES IN THE EFFECTIVENESS OF PUBLIC PROCUREMENT IN INFRASTRUCTURE WORKS IN THE AUTONOMOUS DESCENTRALIZED GOVERNMENT OF CANTON GUARANDA, PROVINCE OF BOLÍVAR, YEAR 2017 "In order for the research process to be successfully developed, a field investigation is carried out, where first approximations are made with the institution in order to identify the problem and acceptance for the realization of this research work, after which a bibliographic research is carried out, with the purpose of theoretically substantiating what concerns this subject and acquire valid knowledge to efficiently carry out the development of this study, making use of methods: inductive and deductive being this a descriptive research techniques were employed and instruments that allow understanding the problem in a general and particular way, obtaining information through the application of surveys addressed to the officials; so that through the interpretation of the results in a quantitative and qualitative way, we can know everything that implies the contracting of works. Once the investigative work is completed, it is established that within this institution there is a discrepancy in what is manifested by executives such as: Mayor and officials in charge of these processes, about the processes demanded by this type of activity, for which it is concluded, that the statement of a procedure manual; to carry out these processes within the GADCG, an instrument that will allow the execution and flow of each stage in the hiring, since the personnel in charge of this area will have a guide that improves or supports what they have been executing, in the same way it is established in a training and training tool for future officials; contributing to an efficient administration of public resources with which the institution has. Keywords: accounting processes public procurement, infrastructure works, guidance.